Epidemiology Of Fatal Burn Cases in G.K. General Hospital, Bhuj - Vaghela , Prithvirajsinh C; Ahir , Ghanshyam N; Patel , Malay H (National Journal of Community Medicine, 2012)
Background: Burn injury cases are one of the common emergencies admitted to any hospital in India. There are several factors, which play a great role in the treatment, management, autopsy and investigations of burns death cases. Objective: The study was aimed to find the epidemiology, pattern of burns deaths and various reasons or factors associated with it. Methodology: The present cross-sectional study of 1504 cases was carried out in Forensic Medicine Department at Gujarat Adani Institute of Medical Sciences, Bhuj from January 2008 to December 2011. Results: The most common cause of death in the majority of the deaths was burns (31.12%) followed by head injury (21.61%), poisoning (11.44%), regional injury (9.37%), drowning (5.12%) and hanging (5.05%). Maximum incidence (82.26%) seen in females. Most of the victims (42.09%) were in the age group of 21-30 years. Most burns were domestic, in low socio-economic class and in house-wives. 74.57% of cases were accidental in nature as per reports. Conclusion: Most of the causes are preventable. The result of this study indicates that, by not only a strong legal support network but also safety precautions, opportunities for essential education and awareness, alternative accommodation and a change in attitude and mind set of society, judiciary, legislature, executive, men and the most importantly women herself can lower or prevent such deaths.